2009
DOI: 10.3390/ma2041908
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Response to Subcutaneously Implanted Recombinant Spider Silk: An in Vivo Study

Abstract: Spider silk is an interesting biomaterial for medical applications. Recently, a method for production of recombinant spider silk protein (4RepCT) that forms macroscopic fibres in physiological solution was developed. Herein, 4RepCT and MersilkTM (control) fibres were implanted subcutaneously in rats for seven days, without any negative systemic or local reactions. The tissue response, characterised by infiltration of macrophages and multinucleated cells, was similar with both fibres, while only the 4RepCT-fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 37 publications
(54 reference statements)
3
80
0
Order By: Relevance
“…In addition, the 4RepCT protein is produced in a heterologous host (Escherichia coli), which enables affordable production and results in products of non-animal origin, both important factors for culture systems intended for clinically compliant applications. For future therapeutic applications, it is also important that 4RepCT based matrices are tolerated and degraded in vivo [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 4RepCT protein is produced in a heterologous host (Escherichia coli), which enables affordable production and results in products of non-animal origin, both important factors for culture systems intended for clinically compliant applications. For future therapeutic applications, it is also important that 4RepCT based matrices are tolerated and degraded in vivo [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies to avoid these problems have been tried, such as the introduction of methionine residues for controlled oxidation/reduction to prevent and promote assembly, respectively [50,65,89], kinase recognition motifs for controlled assembly via enzymatic phosphorylation [54] or solubility-enhancing fusion partners that can be released enzymatically [11]. In the latter case, spontaneous assembly into macroscopic, sterile, pyrogen-free and biocompatible silk-like fibres is possible, with the use of only physiologically compatible solvents [11,90,91] (Fig. 2).…”
Section: Recombinant Spidroin Productionmentioning
confidence: 99%
“…34,38,42 Baoyong et al studied if the recombinant spider silk proteins pNSR-32 and pNSR-16 in the form of porous membranes could be employed as wound dressings on deep burns in rats. The membranes were reported to be as efficient in promoting wound healing as clinically used collagen sponges.…”
Section: Is Recombinant Spider Silk Biocompatible?mentioning
confidence: 99%
“…In the tissue surrounding each fiber bundle the cell population consisted mainly of macrophages and a few FBGC, even though other cell types also were observed. 34 Taken together, it seems like natural or synthetic spider silk implanted in living tissue evoke quite diverse reactions, ranging from mild to severe FBR, and some studies have also shown the presence of chronic inflammation with mononuclear cell infiltrates. The range of reactions observed may not be surprising since the material implanted varies a lot.…”
Section: Is Recombinant Spider Silk Biocompatible?mentioning
confidence: 99%